Pelaksanaan Program REDD+ di Kalimantan Timur - Syafitri, Indriana; Tanjung, Nurul Fitralaila; Purbaningrum, Dini Gandini (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The efforts made by Indonesia in overcoming the problem of deforestation and forest degradation is the REDD+ Program. REDD+ is implemented to reduce the rate of deforestation and reduce emissions and sustainable economic growth. The implementation of REDD+ in East Kalimantan has its own strengths and weaknesses. This study aims to determine the implementation of the REDD+ Program in East Kalimantan. This research uses a library research method with a qualitative approach. In answering questions about the problems of REDD+ implementation in East Kalimantan, this research uses SWOT analysis theory. The results show that the strengths of the REDD+ program are the strong commitment of the East Kalimantan local government, and the initiation of various programs. The weaknesses of the REDD+ program are the lack of long-term funding and conflicts over land ownership. The opportunity of REDD+ program is the increasing economic growth of local communities in East Kalimantan. The threat of REDD+ program is the supervision of law enforcement that has not been fair for all communities in East Kalimantan.